Pengaruh Financial Distress, Opini Auditor Dan Pergantian Manajemen Terhadap Auditor Switching Pada Perusahaan Industri Dasar Dan Kimia Di Bursa Efek Indonesia - Fenny Fenny; Isieny Wendy; Stevanny Stevanny; Tetty Tiurma Uli Sipahutar (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2020)
This research was conducted to identify the effect of Financial Distress, Auditor Opinion, and Management Changes on Auditor Switching in the basic and chemical industry listed on the Indonesia Stock Exchange. The sample is taken by using purposive sampling, where the population amounted to 69 companies, and after deducting the research criteria, the research sample contained 57 companies so that in three years' period amounted to 171 companies. This research simultaneously showed Financial Distress, Auditor Opinion, and Management Changes has a positive effect and significantly towards Auditor Switching. Partially, Financial Distress has a positive effect and significant on Auditor Switching while Auditor Opinion and Management Changes have a negative effect and significant on Auditor Switching.